2014
DOI: 10.1158/1078-0432.ccr-14-0496
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Infectious Etiologies in the Pathogenesis of Marginal Zone B-cell Lymphomas

Abstract: Extranodal marginal zone B-cell lymphomas of the mucosa-associated lymphoid tissue (MALT) arise from lymphoid populations that are induced by chronic inflammation in extranodal sites. The most frequently affected organ is the stomach, where MALT lymphoma is incontrovertibly associated with a chronic gastritis induced by a microbial pathogen, Helicobacter pylori. Gastric MALT lymphoma therefore represents a paradigm for evaluating inflammation-associated lymphomagenesis, which may lead to a deeper understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 107 publications
0
78
0
1
Order By: Relevance
“…Multiple observational studies have consistently reported an increased risk of certain B‐cell lymphomas with hepatitis C virus (HCV) infection . Chronic antigen stimulation of lymphocytes is a hypothesized mechanism in HCV‐associated lymphoma, followed by a second oncogenic or proliferative “hit” that may be antigen independent . Although not as strong and consistent as the associations with lymphoma, HCV has also been associated with many other hematologic malignancies, including myeloma, chronic lymphocytic leukemia, and myeloid leukemias, as well as with monoclonal gammopathy of unknown significance (MGUS), a premalignant precursor of multiple myeloma.…”
mentioning
confidence: 99%
“…Multiple observational studies have consistently reported an increased risk of certain B‐cell lymphomas with hepatitis C virus (HCV) infection . Chronic antigen stimulation of lymphocytes is a hypothesized mechanism in HCV‐associated lymphoma, followed by a second oncogenic or proliferative “hit” that may be antigen independent . Although not as strong and consistent as the associations with lymphoma, HCV has also been associated with many other hematologic malignancies, including myeloma, chronic lymphocytic leukemia, and myeloid leukemias, as well as with monoclonal gammopathy of unknown significance (MGUS), a premalignant precursor of multiple myeloma.…”
mentioning
confidence: 99%
“…In humans, B‐cell lymphomas are thought to occasionally occur in individuals with chronic antigenic stimulation . The cellular signals from other cells in the inflammatory environment provide survival and proliferation signals that may lead to malignant transformation or sustained tumour cell growth . Though these causes more often are described in terms of incidence, they may also play a role in the biologic activity of the tumours they cause.…”
Section: Discussionmentioning
confidence: 99%
“…A brief overview of such treatments is presented in this review, whereas new directions in other lymphoma subtypes are presented in this edition of CCR Focus (83)(84)(85)(86)(87). Among other promising approaches, combining anti-CD20 antibodies with IMiDs, mAbs directed against other surface antigens such as CD22, immunomodulatory antibodies such as PD-1, or inhibitors of the B-cell receptor (BCR) pathway is of paramount interest.…”
Section: Discussionmentioning
confidence: 99%